2022
DOI: 10.1001/jamapsychiatry.2022.0155
|View full text |Cite
|
Sign up to set email alerts
|

Association of Screen Time With Internalizing and Externalizing Behavior Problems in Children 12 Years or Younger

Abstract: IMPORTANCE Currently, there is a lack of consensus in the literature on the association between screen time (eg, television, video games) and children's behavior problems.OBJECTIVE To assess the association between the duration of screen time and externalizing and internalizing behavior problems among children 12 years or younger.DATA SOURCES For this systematic review and meta-analysis, MEDLINE, Embase, and PsycINFO databases were searched for articles published from January 1960 to May 2021. Reference lists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
72
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 159 publications
13
72
3
2
Order By: Relevance
“…The results of the current review largely align with recent systematic reviews on aggregated electronic screen time in children and young people, which have concluded that there are positive small but significant correlations between screen time and young children's internalizing and externalizing behaviours [63,64], and that longitudinal associations between screen time and depressive symptoms varied between different devices and uses [64].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of the current review largely align with recent systematic reviews on aggregated electronic screen time in children and young people, which have concluded that there are positive small but significant correlations between screen time and young children's internalizing and externalizing behaviours [63,64], and that longitudinal associations between screen time and depressive symptoms varied between different devices and uses [64].…”
Section: Discussionsupporting
confidence: 83%
“…We encourage future reviews to conduct meta-analyses of specific MP/WD types of activity and their effects on mental health, as Sohn et al have conducted with PSU [18]. A further consequence of not conducting a meta-analysis is that we were not able to estimate publication bias, evidence of which has been reported in a recent systematic review into child screen time and behaviour problems [63].…”
Section: Limitationsmentioning
confidence: 96%
“…Across the previous studies, most of them focused on overall ST or television watching time instead of distinguishing different types of ST when examining the associations between ST and lifestyle behaviors ( 11 , 35 ). While television viewing remains the most common type of screen-based activities among adolescents, video and computer games have also become part of everyday life for adolescents, television and video/computer games are also the most commonly studied types in screen research ( 36 ). Therefore, more research is needed to explore the associations between different types of ST and lifestyle behaviors, in order to understand how to promote healthy lifestyles from the perspective of limiting specifically diverse ST.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to understand the modifiable risk factors associated with the development of disruptive behavior disorders. Previous studies have described associations between higher screen time and more externalizing behaviors, such as violence and rule-breaking in children, though findings have been mixed, mostly limited to television and video games, and effect sizes were generally small (Carson et al, 2016;Christakis & Zimmerman, 2007;Eirich et al, 2022;Pagani, L evesque-Seck, & Fitzpatrick, 2016;Willoughby, Adachi, & Good, 2012). Exposure to aggressive, inappropriate, or violent content online may lead to similar behaviors offline or further reinforce externalizing behaviors (Bandura, 1977;Ellis, Dumas, & Forbes, 2020).…”
Section: Introductionmentioning
confidence: 99%